2016
DOI: 10.1002/aic.15341
|View full text |Cite
|
Sign up to set email alerts
|

Wetting forces and meniscus pinning at geometrical edges

Abstract: It is shown that complications in currently used optical measurements for wetting and flow resistance over edges can be circumvented by surface tension force measurements. These forces are measured by employing a modified Wilhelmy plate testing technique in which a plate with rectangular holes is immersed. The forces measured during immersion and emersion are subdivided into mass, buoyancy, and surface tension related parts, where the flow resistance when the meniscus passes horizontal faces and edges of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
5
7
0
Order By: Relevance
“…This is attributed to their unique geometry as the sharp edges of the particles require substantially more energy to be engulfed by water resulting in the previously described pinning. This phenomenon has been previously reported 50,51 and is a result of the deformation of the three phase contact line, resulting in an increase in the observed surface tension force normal to the surface at the edge, and consequently the observed contact angle. Furthermore, it has been reported that this increase in force is proportional to the length of the edge in question, explaining the observed behaviour of the liquid on the hydrophilic platelets as they increased in size.…”
Section: Paper Materials Advancessupporting
confidence: 77%
See 1 more Smart Citation
“…This is attributed to their unique geometry as the sharp edges of the particles require substantially more energy to be engulfed by water resulting in the previously described pinning. This phenomenon has been previously reported 50,51 and is a result of the deformation of the three phase contact line, resulting in an increase in the observed surface tension force normal to the surface at the edge, and consequently the observed contact angle. Furthermore, it has been reported that this increase in force is proportional to the length of the edge in question, explaining the observed behaviour of the liquid on the hydrophilic platelets as they increased in size.…”
Section: Paper Materials Advancessupporting
confidence: 77%
“…This is further demonstration of the substantial energy required to overcome the forces attributed to the sharp edge of the platelets, despite the low contact angle of the particles. 50,51 The hydrophobic plates (PET-PPy-C 8 F) demonstrate different behaviour across all three sizes. This is expected due to their greater hydrophobicity and consequently greater ability to stabilise a water droplet and form a liquid marble, as observed in the rolling experiments above (Fig.…”
Section: Electrostatic Experimentsmentioning
confidence: 99%
“…De Wijs et al employed a modified Wilhelmy plate testing technique and measured the force for meniscus shape transitions over edge geometries under quasi-static conditions. Moreover, wetting effects directly linked to surface defects can be detected qualitatively [31]. All these studies show that the pinning of the contact line shows obvious geometric dependence [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 86%
“…1). Our objects being denser than water, the meniscus is therefore pinned on these sharp edges [21]. Pinning means that contact angle is no more a key property of our objects.…”
Section: Methodsmentioning
confidence: 99%